2011
DOI: 10.1002/pfi.20216
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement and performance management in the federal sector

Abstract: Much research has demonstrated that employee engagement is significantly correlated with positive organizational outcomes such as productivity, customer satisfaction, and reduced absenteeism. This article focuses on the importance of effective performance management in driving engagement. The results of a government‐wide survey of federal employees are reported. Every one of the 37 positive performance management practices reviewed was employed more widely in the agencies with the highest percentages of engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…Perceived SES advancement barriers and challenges were experienced individually by men, women, minority men, minority women, and individual minority groups (Bourdon, ; Cabble, ; Hairston, ; Hanson, ; Reid, ; Wilkerson, ; Wirth, ). Employees might experience similar perceived personal barriers and challenges related to limited interest in advancing, an unwillingness to take advantage of leadership development opportunities, or lack of understanding of SES qualification and selection requirements and processes (Marrelli, ; OPM, ; Xu & Thomas, ). However, discrimination, cultural differences, and personal biases might heighten the perceived career advancement barriers and challenges experienced by minorities (Dolan, ; Klein & Wang, ; Wesley, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived SES advancement barriers and challenges were experienced individually by men, women, minority men, minority women, and individual minority groups (Bourdon, ; Cabble, ; Hairston, ; Hanson, ; Reid, ; Wilkerson, ; Wirth, ). Employees might experience similar perceived personal barriers and challenges related to limited interest in advancing, an unwillingness to take advantage of leadership development opportunities, or lack of understanding of SES qualification and selection requirements and processes (Marrelli, ; OPM, ; Xu & Thomas, ). However, discrimination, cultural differences, and personal biases might heighten the perceived career advancement barriers and challenges experienced by minorities (Dolan, ; Klein & Wang, ; Wesley, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees interested in career advancement are more likely to seek a leadership position if they believe the salaries and benefits are compensatory to the level of responsibility and accountability (Tietjen & Myers, ). If SES pay, benefits, and compensation are not appealing (Carey, ; Marrelli, ; OPM, , ; Xu & Thomas, ), minority men and women might be less interested in increasing their level of responsibility and becoming an SES member.…”
Section: Findings and Conclusionmentioning
confidence: 99%
“…Among both public- and private-sector employers, employee engagement is a principal factor in productivity, job satisfaction, higher employee retention, and lower absenteeism. Highly engaged employees are motivated to do their best, place organizational interests above their own, are innovative, and contribute to a collegial work environment (Marrelli, 2011); they often are the top contributors to their organization’s performance (Trahant, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, disengaged employees become focused on tasks rather than outcomes, do not have productive relationships with their managers or coworkers (Fernandez, 2007), have low or no vitality at work, resist change, and usually have a negative outlook (Marrelli, 2011). Disengagement results in high turnover, which costs time and resources spent in hiring replacements, slows productivity while new employees learn on the job, and causes loss of institutional memory (Fernandez, 2007; Fragoso et al, 2016; Liss-Levinson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…But, the study (Baird et al, 2012) with a sample size of 450 respondents of the Australian local council revealed that the PMS was only abstemiously effective when compared to performance related outcomes, and less effective when compared to the achievement of employee linked outcomes. In spite of this, it is interesting to note that in a government-wide survey of federal employees in the United States of America (Marrelli, 2011). All the 37 positive performance management practices reviewed was used widely in the organisations with the highest percentages of engaged employees.…”
Section: Statement Of the Problemmentioning
confidence: 99%